Raspberry Pi for Commercial Applications (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The objective of this paper is to create a low cost commercial off the shelf data analyzer for improving automotive safety and design a user interface infotainment system by using Raspberry Pi.Â  In this paper we propose Raspberry pi based application that monitor the vehicle ECUs through an OBD-II(On Board Diagnostics) interface, perform Diagnostics with DTCs (Diagnostics trouble codes). Infotainment system having functions such as audio and video playback, games, internet connectivity through either USB Wi-Fi dongles or USB Modems and dashboard camera operation. Raspberry Pi will transmit the data over Wi-Fi in real-time in xml format over Wi-Fi on a DHCP connected network.